ANALISIS PERENCANAAN GEDUNG PERPUSTAKAAN STAIN PAREPARE DENGAN MENGGUNAKAN MODIFIKASI METODE FLAT SLAB - Mustakim, Mustakim; Muhammad, Saing (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
The Analysis of Library Building Plan of Sekolah Tinggi Agama Islam Parepare by using A Modication of Flat Slab Method. The research aimed to know the dimensions of main structure, create construction structure using at slab based on ETABS Program that was analyzed according to SNI 2847:2013. Counting the reinforcement needed by main structure and create a nal design based on the modication result of Library Building as well as analyze the mass participation in earthquake areas. The analysis result showed that the thickness of the whole flat floor was 22 cm and drop panel was 120 cm x 120 cm with 12 cm thick, column dimension K1 for Floor 1 with 70/70, K1 floor 2-4 with 60/60, K1 floor 5 with 50/50, column 2 floor 1-5 with 50/35 and K3 floor 1-5 with 30 x 30, the thickness of shear wall was 30 cm. The reinforcement of flat slab produced reinforcement D16 mm, main column reinforcement K1 22D22, column K2 9D22, column K8D12. Final Plan of library building modification based on technical drawing form consisted of the Picture of structure plan, pieces, and detail of the reinforcement. In earthquake area with Category C, it was showed by mass partition control on mode 4 and 5 had achieved 93% and 94% and was able to restrain the load of earthquake plan.